The confession - Todd, Charles (Todd, Charles. Inspector Ian Rutledge novels., 2012)
Troubled Scotland Yard inspector Ian Rutledge wrestles with a startling and dangerous case that reaches far into the past when a false confession from a man who is not who he claims to be leads to a brutal murder.